Aortopathy in the 7q11.23 microduplication syndrome. (26th November 2014) - Parrott, Ashley; James, Jeanne; Goldenberg, Paula; Hinton, Robert B.; Miller, Erin; Shikany, Amy; Aylsworth, Arthur S.; Kaiser‐Rogers, Kathleen; Ferns, Sunita J.; Lalani, Seema R.; Ware, Stephanie M.
<x xml:space="preserve">Abstract</x> The 7q11.23 microduplication syndrome, caused by the reciprocal duplication of the Williams‐Beuren syndrome deletion region, is a genomic disorder with an emerging clinical phenotype. Dysmorphic features, congenital anomalies, hypotonia, developmental delay highlighted by variable speech delay, and autistic features are characteristic findings. Congenital heart defects, most commonly patent ductus arteriosus, have been reported in a minority of cases. Included in the duplicated region is elastin (ELN), implicated as the cause of supravalvar aortic stenosis in patients with Williams–Beuren syndrome. Here we present a series of eight pediatric patients and one adult with 7q11.23 microduplication syndrome, all of whom had aortic dilation, the opposite vascular phenotype of the typical supravalvar aortic stenosis found in Williams–Beuren syndrome. The ascending aorta was most commonly involved, while dilation was less frequently identified at the aortic root and sinotubular junction. The findings in these patients support a recommendation for cardiovascular surveillance in patients with 7q11.23 microduplication syndrome. © 2014 Wiley Periodicals, Inc.